Prenatal folic acid use associated with decreased risk of myelomeningocele: A case-control study offers further support for folic acid fortification in Bangladesh - Kancherla, Vijaya; Ibne Hasan, Md Omar Sharif; Hamid, Rezina; Paul, Ligi; Selhub, Jacob; Oakley, Godfrey; Quamruzzaman, Quazi; Mazumdar, Maitreyi (PloS one, 2017)
Neural tube defects contribute to severe morbidity and mortality in children and adults; however, they are largely preventable through maternal intake of folic acid before and during early pregnancy. We examined the association between maternal prenatal folic acid supplement intake and risk of myelomeningocele (a severe and common type of neural tube defect) in the offspring. We performed secondary analysis using data from a case-control study conducted at Dhaka Community Hospital, Bangladesh between April and November of 2013. Cases and controls included children with and without myelomeningocele, respectively, and their mothers. Cases were identified from local hospitals and rural health clinics served by Dhaka Community Hospital. Controls were selected from pregnancy registries located in the same region as the cases, and matched (1:1) to cases by age and sex. Myelomeningocele in the offspring was confirmed by a pediatrician with expertise in classifying neural tube defects. Maternal prenatal folic acid supplement intake was the main exposure of interest. We estimated crude and adjusted odds ratios (OR) and 95% confidence intervals (CI) using conditional logistic regression analysis. There were 53 pairs of matched cases and controls in our study. Overall, 51% of case mothers reported using folic acid supplements during pregnancy compared to 72% of control mothers (p = 0.03). Median plasma folate concentrations at the time of study visit were 2.79 ng/mL and 2.86 ng/mL among case and control mothers, respectively (p = 0.85). Maternal prenatal folic acid use significantly decreased the odds of myelomeningocele in the offspring (unadjusted OR = 0.42, 95% CI = 0.18-0.96). The association was slightly attenuated after adjusting for maternal age at the time of pregnancy (adjusted OR = 0.43, 95% CI = 0.18-1.02). Our study confirms the protective association between maternal prenatal folic acid supplement use and myelomeningocele among children born in Bangladesh. Our findings point to an overall low folic acid supplement use and low plasma folate concentrations among women of reproductive age in Bangladesh. Mandatory fortification of staple foods with folic acid can address low folate status among women of child-bearing age, and prevent child morbidity and mortality associated with myelomeningocele in Bangladesh.